Diet composition of the Pharaoh Eagle Owl, Bubo ascalaphus (Strigiformes, Strigidae) in a Steppe region of Algeria - Benamor Naceur (Sciendo, 2021)
The diet composition of Pharaoh Eagle Owl (Bubo ascalaphus) was investigated in a semiarid area of North-western Algeria. A total of 65 pellets regurgitated by the B. ascalaphus were analysed, 288 food items were composed primarily of mammal remains (4 rodents, 1 bat and insectivore, 93.7%), and 1 bird species (passerine, 6.3%). The most frequent prey among the mammals were rodents (83.3%), which included Mus musculus (59.7%), Meriones shawi (11.1%), Meriones libycus (11.1%) and Jaculus jaculus (1.4%). The rodents were the most important prey items in biomass (91.4%), M. shawi made up to 41.9% of the total biomass. We may conclude that the Pharaoh Eagle Owl relies, in its feeding, very broadly on small mammals, completed by other groups.